Is Cancer Immunotherapy More Hype Than Hope? - Ronny Lesmana; Edward J Hadi; Hanna Goenawan (Journal of Medicine and Health, 2020)
The immunosurveillance system in the human body can detect and eradicate abnormal cells. However, cancer cells can avoid immune destruction by exploiting the immunosuppression system. Extensive research has been done to find therapeutic agents that could reverse this condition. Novel drugs called checkpoint inhibitors have been developed and showed a promising result. Besides, “living’’ drug, an engineered T-cells which can accurately target cancer cells, has increased public attention in immunotherapy. These immunotherapies might bring a new era of cancer management, a highly effective and specific treatment with fewer adverse effects. Keywords: Immunosurveillance; T-Cell; Therapeutic agents; Immunotherapies